Análise da expressão gênica como parâmetro da eficácia terapêutica da levotiroxina em pacientes com hipotiroidismo primário - Silva, Valdelena Alessandra da (2016)
Hypothyroidism is the inadequate production of thyroid hormone or the inappropriate action of thyroid hormone on target tissues. Among thyroid dysfunctions, hypothyroidism is the most common disorder in the general population, particularly in women. Levothyroxine sodium (L-T4) is considered the drug of choice and most effective as a replacement or supplementation treatment in patients with hypothyroidism worldwide. The aim of this study was to provide a panel of gene expression to mark the therapeutic response of levothyroxine in patients with primary hypothyroidism. We selected 4 control subjects and 8 subjects with levothyroxine therapy, 4 of whom were euthyroid with adequate treatment, with serum TSH between 0.4mIU/L and 4.0mIU/L, and 4 subclinical hypothyroidism with inadequate treatment with TSH Between 4.1mIU/L and 20.0mIU/L. Samples of 5mL of venous blood were collected and stored in PAXgene RNA tubes. RNA extraction was performed with the PAXgene RNA extraction kit (Qiagen). The transcriptome library was created on an NGS platform, Ion AmpliSeq Gene human transcriptome. Mann-Whitney was used to compare the two groups. Continuous variables are presented as median, minimum and maximum values, and Kruskal-Wallis was used to compare the three groups. Correlation between transcripts, TSH and Zulewski: Spearman's method. The data analyzed using IBM SPSS Statistics. The computational data analysis was performed in software RStudio, Package EdgeR v 3.12.0 of Bioconductor. Significant genes are calculated after a False Discovery Response (FDR) setting. A p<0.05 was considered significant. Differential expression analysis revealed 179 with increase and 174 with decrease in expression, being 289 mRNA and 64 non-coding RNA. Of these, 2 genes (CXCR6 and HTR4) showed an absolute value of the reads relatively high. We constructed a panel capable of identifying patients with an inadequate response to levothyroxine treatment. We identified transcripts that could compose a panel for the evaluation of gene expression, serving as biomarkers for the diagnosis of primary hypothyroidism, even in individuals with TSH concentrations close to the reference values. In addition to marking the response to the use of levothyroxine, CXCR6 and HTR4, they may be useful in evaluating the tissue repercussion of hypothyroidism.